The Effect of Numbered Heads Together (NHT) on Elementary School Students’ Mathematical Problem-Solving Ability in Geometry - Fikri Fathony Ahsan (Universitas Wiralodra, 2025)
Within the framework of mathematics learning at the elementary school level-particularly in geometry-many students still struggle to fully understand the material and experience difficulties in problem-solving. They often focus on achieving the final answer without a deep understanding of the problem-solving process. This study aims to examine the effect of the cooperative learning approach, specifically the Numbered Heads Together (NHT) model, on the mathematical problem-solving abiities in geometry of fifth-grade students at a state elementary school in Central Jakarta. The research employs a quantitative method with a quasi-experimental design. Data were gathered through a test comprising 10 essay questions. The analysis involved tests for normality, homogeneity, and hypothesis testing. Post-test scores exceeded pre-test results, demonstrating the effectiveness of the NHT model. The significance value of the t-test (p < 0.005) indicates that H₀ is rejected and H₁ is accepted, showing that the NHT model significantly influences fifth-grade students' mathematical problem-solving ability.